Coffee Commodity Development: An Effort to Accelerate Diversification of Food Consumption Based on Local Resources in Central Aceh Regency - Muhammad Rizki; Ramadhan Razali (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2023)
This research discusses the Development of Coffee Commodities as an Effort to Accelerate Diversification of Food Consumption Based on Local Resources in Central Aceh Regency. This research aims to analyze the development of coffee commodities as an effort to accelerate the diversification of local resource-based food consumption in Central Aceh Regency. Central Aceh Regency has great potential in coffee production, but the limited diversification of local food consumption is one of the problems that need to be overcome. This research uses a descriptive method with a qualitative approach to collect data from various sources, such as field surveys, interviews, and documentation of data analysis used in this research primary and secondary data. Based on the results of the study it was found that: The development of coffee commodities as an effort to accelerate the diversification of local resource-based food consumption in Central Aceh District has great potential. By utilizing the favorable geographical conditions and diversity of coffee varieties, high quality coffee can be produced which is one of the alternatives for local food consumption. However, challenges such as lack of market access, lack of promotion, limited infrastructure, as well as climate change and pest attacks, need to be addressed through collaborative efforts between coffee farmers, local government, and other stakeholders